Structural behavior of GFRP-concrete composite beams (Fracture and Structural Integrity, 2025)
Glass Fiber Reinforced Polymer (GFRP) I-sections offer a promising alternative to traditional steel reinforcement due to their reduced weight and maintenance requirements. This study aims to optimize the design of GFRP-reinforced composite concrete beams for cost-effective solutions. Twelve tested beams were tested under four-point bending loading, divided into four groups with varying depths: three conventional reinforced concrete (RC) beams as control specimens; nine beams with GFRP I-sections positioned internally; externally; and internally with exposure to 500°C for 90 minutes. The test results indicate that GFRP-reinforced beams exhibit superior strength and bending resistance compared to conventional RC beams where an increase in maximum load ranging from 62% to 113% and reduced deflection at the same load level. Optimal performance was observed when GFRP I-sections were placed near the tensioned fiber. Exposure to elevated temperatures resulted in minimal performance reductions, not exceeding 5% at yield load and 16% at maximum load comparing with composite tested specimens without exposure to elevated temperature. Theoretical analyses closely aligned with experimental results, providing a foundation for practical guidelines on the economical design of GFRP-reinforced composite.
Keywords: GFRP I-Section; Composite beams; Reinforced concrete; Analysis; Experimental and theoretical study; Concrete-Filled Steel Tube Columns; Impact load; Fire